Human Resource Management in the Enhancement Processes of Knowledge Management - Sundiman, Didi (Binus Business Review, 2017)
This research explored Human Resource Management (HRM) in enhancement processes of knowledge management. This research explored how HRM practice enhanced the operational of knowledge management. Data were collected by a survey by interviewing 12 informants from Small and Medium Enterprise (SME). The results show that HRM practice gives initiative in the enhancement process of the knowledge management strategy applied to the company. It can be concluded that each sub-component of HRM affects the components of knowledge management, and HRM is highly influential and has a positive effect on quality management processes and vice versa in the work environment.